2014
DOI: 10.1016/j.amjcard.2014.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Activity Level on Biomarkers of Inflammation and Insulin Resistance Over 5 Years in Outpatients With Coronary Heart Disease (from the Heart and Soul Study)

Abstract: Higher levels of physical activity are associated with lower rates of coronary heart disease (CHD). Prior studies suggest this is partly due to lower levels of inflammation and insulin resistance. We sought to determine whether physical activity level was associated with inflammation or insulin resistance during a 5-year period in outpatients with known CHD. We evaluated 656 participants from the Heart and Soul Study, a prospective cohort study of outpatients with documented CHD. Self-reported physical activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Consistent with previous literature, we observed that those with lower income and educational attainment had lower adherence to the HLS [10, 11]. Although having higher socioeconomic and educational status can help support a healthy lifestyle environment, in our analysis the HLS remained significantly associated with inflammatory markers even after adjusting for such factors.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with previous literature, we observed that those with lower income and educational attainment had lower adherence to the HLS [10, 11]. Although having higher socioeconomic and educational status can help support a healthy lifestyle environment, in our analysis the HLS remained significantly associated with inflammatory markers even after adjusting for such factors.…”
Section: Discussionsupporting
confidence: 90%
“…The evidence for physical activity and inflammation is inconsistent; while some studies have reported an association with CRP and IL-6 independent of BMI [10, 11, 29], others found no association or the association was null when adjusted for adiposity markers [24, 26, 30]. Furthermore, we found that IL-6 was associated individually with physical activity and sedentary behavior, and with social support, but that these associations were attenuated when adjusted for the other components of the HLS, suggesting that they were not independent of the other lifestyles behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Point values ranged from 0 to 5, with higher scores indicating greater physical activity. This one-item measure of physical activity was predictive of subsequent inflammation, insulin resistance, cardiovascular events, and mortality in this cohort (4,25). Self-reported physical activity has been shown to be a valid and reliable assessment of physical activity (2628).…”
Section: Methodsmentioning
confidence: 78%
“…There is compelling evidence supporting the role of inflammatory responses in the pathophysiology of depression (57). Physical inactivity, inadequate sleep, and other unhealthy behaviors can lead to elevated inflammation (25) and thus contribute to the development and exacerbation of depressive symptoms. On the other hand, specific symptoms of depression—including loss of interest, hopelessness, fatigue, and trouble remembering—may reduce one’s motivation or ability to maintain physical activity and medication regimens.…”
Section: Discussionmentioning
confidence: 99%